Способи входження філософського знання в тканину педагогічної теорії та педагогічних практик - Возняк, Володимир; Voznyak, Volodymyr; Буцяк, Ірина; Bucyak, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано взаємозв’язок філософії та педагогіки, при цьому стверджено безперспективність так званого «міждисциплінарного підходу». Аргументовано думку, що філософські ідеї адекватно входять у тканину і теоретичної, і практичної педагогіки у вигляді діяльної здатності суб’єкта. The educational process in Ukraine objectively needs philosophical reflection especially in the sphere of relations of philosophy and pedagogics. Objectives: the critical analysis of the «interdisciplinarity» phenomenon and finding out the ways of integrating the philosophical knowledge into pedagogics. The classical methodology of dialectical logic with using the ideas of E. V. Ilienkov school. The main conclusion points on the unreasonableness of the so-called «interdisciplinar approach» because of interdisciplinary communication’s being in its present state the twisted form of the real scientific communication. The authors pay attention to P. Natorp’s idea of pedagogics as the concrete philosophy. While being integrating into the pedagogical field philosophy is not being «used» but reaches the universality. Moreover: philosophical ideas integrate into the pedagogical theory and practice as the acting ability of a person.
Integrating the Philosophical Knowledge Into the Pedagogical Theory and Practice
Keywords: філософія; philosophy; педагогіка; pedagogics; конкретність; concreteness; інституалізація; institutionalization; педагогічне мислення; pedagogical thinking; діяльна здатність; acting ability